2013
DOI: 10.1007/s00408-012-9446-0
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Role of Galectin-9 in the Pulmonary Fibrosis of Patients with Interstitial Pneumonia

Abstract: Our findings suggest that the expression level of Gal-9 in the lung is increased in patients with CVD-IP and that Gal-9 may have a protective role against pulmonary fibrosis of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…We previously demonstrated that Gal-9 was strongly expressed in lymphocytes accumulated into the lung of patients with IP [16]. In line with previous study, Gal-9 levels significantly correlated with absolute lymphocyte Fig.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We previously demonstrated that Gal-9 was strongly expressed in lymphocytes accumulated into the lung of patients with IP [16]. In line with previous study, Gal-9 levels significantly correlated with absolute lymphocyte Fig.…”
Section: Discussionsupporting
confidence: 90%
“…These findings suggest that Gal-9 has a role in local lung inflammation in patients with IP. Further, increased levels of Gal-9 in the lungs of IP patients may protect against pulmonary fibrosis by inhibiting the proliferation of lung fibroblasts and inducing their apoptosis [16]. In the present study, we found increased Gal-9 levels in the BALF of patients with COP, which has the best prognosis among IIPs, compared with IPF, which has the worst prognosis among IIPs.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Human studies indicate a correlation between galectin 3 levels and ESRD, pulmonary fibrosis, heart disease and cancer 153 . Galecto Biotech is currently developing galectin-3 inhibitors for the treatment of fibrosis, specifically IPF 154 . It will be interesting to also investigate their effects on kidney disease progression.…”
Section: Targeting Fibrosismentioning
confidence: 99%